Assessment of the Readiness of Teachers for Developing Students’ Skills in Speaking English through the Use of the “Zoom” Platform - Maming, Jimmy Bernabe; Maravilla, Wes Harven G. (Future Science / FSH-PH Publications, 2022)
Online learning platforms such as “Zoom” platform enable teachers who want to teach a second language like English without having to leave home, especially during the height of the (COVID-19) pandemic in the Kingdom of Thailand. The researcher investigated the readiness of English teachers for the employment of skills needed for online classes. The mixed method (quantitative and qualitative) research strategy was adopted in this study with the questionnaire as the main tool supported by interviews and observation. The data gathered researcher utilized the following statistical tools/formula: frequency, mean distribution, standard deviation, coefficient of variation, and t-test. 1. Thirty-one (31) to 40 years old have the greatest number of respondents; 48 out of the 90 or 53.3% of the respondents are female and 42 out of the 90 or 46.7% of the respondents are male, and most of the respondents are teaching Primary 1 and 2. conducting small-group projects in an online class is the most experienced challenge encountered by the teachers in teaching the English Language through the “Zoom” platform. The study's findings are considered helpful in increasing institutional support for faculty development plans that will help faculty members transition from traditional methods to virtual ones.